Optimized antianginal therapy: a randomized, comparative study of long-acting isosorbide-5-mononitrate and isosorbide dinitrate in patients with coronary heart disease and stable effort angina - Yu. E. Semenova; E. V. Alimova; N. A. Dmitrieva; M. P. Kozyreva; I. P. Konyakhina; Yu. V. Lukina; S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика)
Aim. To compare effectiveness and tolerability of a regular treatment with two nitrates – moderately long-acting isosorbide dinitrate and very long-acting isosorbide-5-mononitrate – in patients with coronary heart disease (CHD) and stable effort angina. Material and methods. The study included 30 patients with verified CHD: 4 females, 26 males; mean age 50.5 years. In total, 21 participants had myocardial infarction (MI) in anamnesis, including 3 with recurrent MI. At coronaroangiography, 6 individuals had coronary stenosis of ≥75%, in at least one artery. Mean duration of stable angina was 8.2 years; 21 patients had functional class (FC) II angina, and 9 – FC III angina, by Canadian Cardiology Association’s classification. Pharmacodynamics was studied in placebo, isosorbide-5-mononitrate, and isosorbide dinitrate treatment regimens. Antianginal and antiischemic effects were assessed by increased physical stress (PS) tolerance – increased time before moderately intensive angina episode, by at least 120 s, comparing to placebo. Each drug was administered for 4 weeks, control period between the courses lasted for 7 days. Results. All patients regularly received individually selected doses of antianginal medications. The therapy was associated with statistically significant increase in all PS tolerance parameters, measured one hour after medication’s intake, comparing to placebo. Isosorbide-5-mononitrate and isosorbide dinitrate treatment was associated with 14 and 18 adverse events, respectively. Conclusion. In CHD patients with FC II-III stable effort angina, isosorbide-5-mononitrate therapy (in an individual dose, once per day) demonstrated a clear, sustained antianginal effect, was well-tolerated, and did not cause clinically manifested tolerance.